Pengaruh Media Sosial terhadap Pola Pikir Anak Usia SD - Challysta Adelia; Adrias Adrias; Aissy Putri Zulkarnaini (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This research aims to examine the impact of social media on the mindset of children at the elementary school level. The method applied is a literature review by analyzing journals, articles, and books relevant to the topic. The findings indicate that social media significantly affects children’s way of thinking, both in positive and negative ways. Positively, it can improve communication abilities and social interaction. However, when used without proper supervision, it may reduce self-confidence, trigger aggressive behavior, and hinder direct social interaction. This study is expected to enrich understanding of the influence of social media on children’s mindsets and serve as a reference for parents, teachers, and educators in formulating effective strategies to minimize potential negative impacts.